2012
DOI: 10.1002/stem.1011
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Coding Mutation Rate During the Reprogramming of Human Somatic Cells into Induced Pluripotent Stem Cells

Abstract: Mutations in human induced pluripotent stem cells (iPSCs) pose a risk for their clinical use due to preferential reprogramming of mutated founder cell and selection of mutations during maintenance of iPSCs in cell culture. It is unknown, however, if mutations in iPSCs are due to stress associated with oncogene expression during reprogramming. We performed whole exome sequencing of human foreskin fibroblasts and their derived iPSCs at two different passages. We found that in vitro passaging contributed 7% to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
148
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(155 citation statements)
references
References 24 publications
7
148
0
Order By: Relevance
“…Only certain aberrations are common. Detailed analysis of single-nucleotide changes suggested that most mutations in iPSCs occur during reprogramming and selection of rare mutants in the original cell population (69,70). Mouse iPSCs were shown to have a significantly lower mutation rate compared with human cells (71).…”
Section: Challenges To Be Addressed In Preclinical Studiesmentioning
confidence: 99%
“…Only certain aberrations are common. Detailed analysis of single-nucleotide changes suggested that most mutations in iPSCs occur during reprogramming and selection of rare mutants in the original cell population (69,70). Mouse iPSCs were shown to have a significantly lower mutation rate compared with human cells (71).…”
Section: Challenges To Be Addressed In Preclinical Studiesmentioning
confidence: 99%
“…Reprogramming stress induced by oncogenic factors and long-term exposure to trypsin during in vitro culture have been shown to increase the susceptibility of fibroblasts to chromosomal mutations. 32,33 Trypsin passaging may contribute to preferential selection of karyotypically abnormal cells within the culture, which are initially rare but over time acquire a growth advantage over normal cells due to mutations that favor their survival and growth during reprogramming. The effect of long-term exposure of human pluripotent stem cells to Accutase has not been widely investigated, but a recent study by Stover and Schwartz reported no abnormalities in the karyotype after .20 passages.…”
mentioning
confidence: 99%
“…To analyze all coding-gene mutations, wholeexome sequencing was performed on hiPSCs following 0.4-Gy g-radiation compared with no radiation. Early passage 4 hiPSCs were used to avoid possible mosaic genotypes acquired during passaging [25][26][27][28]. Sorting and clonal expansion from single cells in parallel was used to isolate individual mutations (Fig.…”
Section: Ldi Does Not Lead To Mutagenic Events In Human Pscsmentioning
confidence: 99%
“…Clones were expanded for three passages, at which time DNA was collected for whole-exome sequencing. Mutations that may have occurred during reprogramming [28] and that were present in passage 4 cells and in irradiated and nonirradiated clones were subtracted as background. Results revealed that radiation produced no gross differences in the number of SNVs and indels between irradiated clones and nonirradiated controls (Fig.…”
Section: Ldi Does Not Lead To Mutagenic Events In Human Pscsmentioning
confidence: 99%